I have a question: $$p^{2}x+q^{2}y = z.$$

I formed the Charpit auxiliary equation as follows

$$ \frac{\mathrm{d}x}{2px} = \frac{\mathrm{d}y}{2py} = \frac{\mathrm{d}z}{2(p^2x + q^2y)} = \frac{\mathrm{d}p}{p-p^2} = \frac{\mathrm{d}q}{q-q^2}.$$

After forming the equation I was unable to solve further (I applied everything I was taught). So I did some research (checked several books, and on the website as well) and found the next step to be

$$\frac{p^2\,\mathrm{d}x + 2px\,\mathrm{d}p}{p^2x} = \frac{q^2\,\mathrm{d}y + 2qy\,\mathrm{d}q}{q^2y}. \tag{1}$$

After which I was able to solve. But I can not understand how they derived the relation (1). Can someone explain what method they applied here?

Disclaimer: The course we are being taught is engineering mathematics.


Charpit's equation: $$\boxed{\frac{dx}{2px} = \frac{dy}{\color{red}{2qy}} = \frac{dz}{2(p^2x + q^2y)} = \frac{dp}{p-p^2} = \frac{dq}{q-q^2}}$$ We have from Charpit's equation $$\frac{dy}{2qy} =\frac{dq}{q-q^2}$$ Rearranging terms $$(q-q^2){dy} =2qy{dq}$$ $$q{dy} =2qy{dq}+q^2dy$$ $$\text { (1) }\frac{dy}{qy} =\frac {2qy{dq}+q^2dy}{q^2y}$$ We have also from Charpit's equation that : $$\frac{dx}{2px} = \frac{dp}{p-p^2}$$ $${dx}{(p-p^2)} = 2px{dp}$$ $${pdx} = 2px{dp}+p^2dx$$ $$\text { (2) }\frac {dx}{px} = \frac {2px{dp}+p^2dx} {p^2x}$$ We use a third equality from Charpit's equation $$\frac {dx}{2px}=\frac{dy}{2qy} \implies \frac {dx}{px}=\frac{dy}{qy} $$ Therefore $$\boxed{\frac{p^2\,\mathrm{d}x + 2px\,\mathrm{d}p}{p^2x} = \frac{q^2\,\mathrm{d}y + 2qy\,\mathrm{d}q}{q^2y}}$$ That you can easily integrate...


Note that the middle term is equal to $\frac{dz}{2z}$ and use it as the reference value. Then $$ \frac{p^2dx}{p^2x}=\frac{pdz}{z},\quad \frac{2px\,dp}{p^2x}=\frac{2dp}{p}=\frac{(1-p)\,dz}{z} \implies \frac{d(p^2x)}{p^2x}=\frac{dz}{z} $$ and similarly for $q^2y$.

Some other obvious simple steps are to recognize the decoupled nature of $$ \frac{dz}{2z}=-\frac{d(1/p)}{1/p-1}=-\frac{d(1/q)}{1/q-1} $$ which integrates to $$ \frac12\ln|z|=c_1-\ln|1/p-1|=c_2-\ln|1/q-1| \\\iff\\ \sqrt{|z|}=C_1\frac{p}{1-p}=C_2\frac{q}{1-q} $$ Then insert $$ p=\frac{\sqrt{|z|}}{C_1+\sqrt{|z|}},\qquad q=\frac{\sqrt{|z|}}{C_2+\sqrt{|z|}} $$ into the first three relations $$ \frac{dx}{2xp}=\frac{dy}{2yq}=\frac{dz}{2z} $$ which should then be easy to integrate.

Or alternatively, combine the $x$ and $p$ fractions to $$ \frac{dx}{x}=\frac{2dp}{1-p}\implies x(1-p)^2=a, $$ and similarly $$ \frac{dy}{y}=\frac{2dq}{1-q}\implies y(1-q)^2=b. $$

  • $\begingroup$ Can you explain as to how we got the relation (1) mentioned in the question. Also what do you mean by decoupled nature? Please explain, knowing that I have a undergraduate understanding of PDEs. $\endgroup$ – Mohammed Arshaan Mar 3 '18 at 12:08
  • $\begingroup$ Also what method is being applied here to transform the auxiliary equations? As far as I can see they are not simple addition, subtraction, multiplication or division operations... $\endgroup$ – Mohammed Arshaan Mar 3 '18 at 12:09
  • $\begingroup$ The first transformations are exactly that, simple arithmetic operations. Note that $p-p^2=p(1-p)$. As both expressions in (1) are equal to $\frac{dz}{z}$, they are also equal to each other. $\endgroup$ – LutzL Mar 3 '18 at 12:16
  • $\begingroup$ Or did you question $d(p^2x)=p^2\,dx+2px\,dp$? $\endgroup$ – LutzL Mar 3 '18 at 12:16
  • $\begingroup$ No. What I mean is that in relation (1) (marked in my question). How did we get the following relation: $$\frac{p^2\,\mathrm{d}x + 2px\,\mathrm{d}p}{p^2x} = \frac{q^2\,\mathrm{d}y + 2qy\,\mathrm{d}q}{q^2y}. \tag{1}$$ $\endgroup$ – Mohammed Arshaan Mar 3 '18 at 12:18

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.